Eko-Spiritualisme: Sebuah Keniscayaan pada Era Kontemporer - Frederikus Fios (Bina Nusantara University, 2013)
This paper provides a new perspective of looking at our natural environment with a spiritual perspective. The main argument of this paper was inspired by the emergence of the reality of our natural environment is increasingly damaged by the implications of a variety of viewpoints, attitudes and human behavior are destructive and counterproductive. The influences of modern science and philosophy have reduced logical meaning of the universe solely on technical functions-economical to fulfill the needs of humans (anthropocentric). In effect, we are witnessing the natural environment is being weakened only in different parts of the world. So this paper is an effort to return to the community awareness of the contemporary world that still cares for the future of our natural environment better. This paper provides an alternative framework as well as a new optimism for our natural environment lasting and sustainable return by optimizing intrinsic qualities inherent in every human being as a spiritual being. Then become eco-spiritual as a necessity for our contemporary world society today.